2011
DOI: 10.1093/annonc/mdq557
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of interim PET response criteria in paediatric Hodgkin's lymphoma—results for dedicated assessment criteria in a blinded dual-centre read

Abstract: The iPET interpretation assured low interobserver variability. High sensitivity for identification of pHL patients suffering relapse is achieved if [18F]-fluorodeoxyglucose uptake above the MBPS value is rated as a PET-positive finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 28 publications
2
30
0
Order By: Relevance
“…[17][18][19][20][21] Response assessment with the 5-PS has been reported by a number of investigators to have good interobserver agreement in a training set of 50 patients, 22 in a study of 260 advanced HL patients with international expert readers, 23 and in pediatric HL. 24 The 5-PS also improves the positive predictive value of PET compared with previous International Harmonization Criteria. 25 These studies, however, were all retrospective, and the 5-PS was not used to direct therapy.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…[17][18][19][20][21] Response assessment with the 5-PS has been reported by a number of investigators to have good interobserver agreement in a training set of 50 patients, 22 in a study of 260 advanced HL patients with international expert readers, 23 and in pediatric HL. 24 The 5-PS also improves the positive predictive value of PET compared with previous International Harmonization Criteria. 25 These studies, however, were all retrospective, and the 5-PS was not used to direct therapy.…”
Section: Introductionmentioning
confidence: 91%
“…7 PET-CT is recommended for response assessment in FDGavid lymphomas using the 5-PS. 34 The 5-PS has good interobserver agreement 22,24,25,[35][36][37] and is predictive of patient outcomes, 29,35,[38][39][40] especially in advanced HL. 37,41 An advantage of the 5-PS is that the threshold used to define complete metabolic response can be altered according to the clinical context or research question.…”
Section: 10-14mentioning
confidence: 99%
“…The value of mid-treatment 18F-FDG PET is also confirmed for Hodgkin disease (HD) (Furth et al 2010;Zaucha et al 2009;Markova et al 2008Markova et al , 2009aEich et al 2008a, b;Krochmalczyk et al 2008). It is recommended to use 18F-FDG PET scanning after 4 cycles of BEACOPP regimen (PET-4).…”
Section: Hodgkin Diseasementioning
confidence: 93%
“…Another study on diffuse large B-cell lymphoma, by Itti et al, found lower interobserver agreement with D5PS (k 5 0.66) than with a semiquantitative counterpart based on SUV max (k 5 0.83) (55). In larger standardized studies of HL that used D5PS, Barrington et al, Furth et al, and Gallamini et al reported k-values of 0.79-0.85, 0.748, and 0.69-0.84, respectively, proving its superiority (56)(57)(58). The implications of these findings on the reproducibility and clinical applicability of the Lugano classification have yet to be determined in prospective studies with large datasets.…”
Section: Methodologic Comparison Of Existing Response Assessment Critmentioning
confidence: 99%